A Performance Profile of Learner Completion and Retention in Australian Vet MOOCs - Paton, Rachael M. [Verfasser]; Scanlan, Joel D. [Verfasser]; Fluck, Andrew E. [Verfasser] (My University, 2018)
"The uptake of Massive Open Online Courses (MOOCs) has been substantial and they continue to flourish as an educational delivery model. Much of the available literature regarding student retention and completions in MOOCs comes from university-designed courses. The Vocational Education and Training (VET) sector has lagged behind its university counterparts as VET pedagogy relies heavily on skills acquisition and does not lend itself as easily to MOOC delivery. This paper analysed the attributes of 366,099 enrolled learners and 132,867 learners that were designated as 'starters' from 263 Australian universities, 27 transnational universities and 73 VET MOOCs to compare the differences in learning environments and to build a VET MOOC learner profile. The findings indicated that higher levels of VET MOOC learners were retained when compared to university MOOCs. It also revealed eight course design factors that may contribute to increased learner retention and completions for VET MOOCs." (author's abstract ; BIBB-Doku)
Keywords: L 4.2.3 Internetbasiertes Lernen / E-Learning; I 2.3.5 Australien, Ozeanien; Berufsbildung; MOOC (Massive Open Online Courses); Leistungsverhalten; Lernplattform; Verzahnung beruflicher und hochschulischer Bildung; Australien